Kearifan Lokal dalam Novel ‘Sayat-Sayat Sunyi’ Karya S.Gegge Mappangewa : Local Wisdom in the Novel 'Sayat-Sayat Sunyi' by S. Gegge Mappangewa - Nurrahmawanda, Nurrahmawanda; Hamsa, Akmal; Usman, Usman (Journal Studies in Indonesian Language and Literature, 2025)
This study aims to identify the forms of local wisdom and the values of local wisdom in the novel